National Mass Gathering Pharmaceutical Care Program at MOH in Saudi Arabia - Ahmed Alomi, Bsc. Pharm, Msc. Clin Pharm, BCPS, BCNSP, DiBA, CDE, Yousef (Journal of Pharmacy Practice and Community Medicine)
Performing Hajj is considered the fifth pillar of Islam at a specific time each year 5-10 days. During this period million of pilgrims gathering in small location addition another thing called Omra with mostly little resemble performance of Hajj is one of excellent with some people. WHO indicted mass gathering if there are more 1000 person in one place at the same time.[1] This is precisely in Hajj and Omra gathering. Each year the number of pilgrims each year ranging of 1,980,249-3,161,573 based on statistics years 2006-2014. Those pilgrims divide into two types of pilgrims who come from inside Saudi Arabia. It is account ranging of 600,718-1,408,641 pilgrims. The second category called outside pilgrims who come from outside Saudi Arabia; it is ranging 1,379,531-1,828,195 pilgrims. [2] Ministry of Health (MOH) provides excellent health care services to those pilgrims. In 2014; for instance, but not limited to these are, Seventeen permanent hospitals, eight seasonal (temporary) general hospitals, 44 permanent primary health center, 114 seasonal (temporary) primary health care centers.